How secure is your building?. Issue 3 (March 2015) - Tankard, Colin
Abstract : Buildings today often incorporate the use of a building automation system, which provides automated centralised control of systems such as heating, ventilation, air conditioning and lighting. Buildings that employ such systems are often referred to as smart buildings. According to AutomatedBuildings, a smart building is defined as one that incorporates "the use of networked technology, embedded within architecture to monitor and control elements of the architecture for exchange of information between users, systems and buildings." 1 So-called smart buildings make use of networked technology to connect a broad range of systems to central management consoles for more efficient operation. This use of networked technology has advantages for security as well, enabling feeds from security controls to be fed into the central management system so that anomalies in traffic flows can be seen and remedial action taken in an efficient, automated manner, as Colin Tankard of Digital Pathways explains.